Impact of the National Health Insurance Coverage Policy on the Utilisation and Accessibility of Innovative Anti-cancer Medicines in China: An Interrupted Time-Series Study - Wenqing Fang; Xinglu Xu; Yulei Zhu; Huizhen Dai; Linlin Shang; Xin Li; Xin Li; Xin Li (Frontiers Media S.A., 2021)
Objective: The study aimed to evaluate the impact of the National Health Insurance Coverage (NHIC) policy on the utilisation and accessibility of innovative anti-cancer medicines in Nanjing, China.Methods: We used the adjusted World Health Organisation and Health Action International methodology to calculate the price and availability of 15 innovative anti-cancer medicines included in the National Health Insurance drug list in 20 tertiary hospitals and six secondary hospitals in Nanjing before and after NHIC policy implementation. Interrupted time-series regression was used to analyse the changes in the utilisation of the study medicines.Results: The price reduction rates of innovative anti-cancer medicines ranged between 34 and 65%. The mean availability rate was 27.44% before policy implementation and increased to 47.33% after policy implementation. The utilisation of anti-cancer medicines suddenly increased with a slope of 33.19-2,628.39 when the policy was implemented. Moreover, the usage rate of bevacizumab, bortezomib, and apatinib significantly increased (p < 0.001, p = 0.009, and p < 0.001, respectively) after policy implementation. With regard to price reduction and medical insurance reimbursement, the medicines became more affordable after policy implementation (0.06-1.90 times the per capita annual disposable income for urban patients and 0.13-4.46 times the per capita annual disposable income for rural patients).Conclusion: The NHIC policy, which was released by the central government, effectively improved the utilisation and affordability of innovative anti-cancer medicines. However, the availability of innovative anti-cancer medicines in hospitals remained low and the utilisation of innovative anti-cancer medicines was affected by some factors, including the incidence of cancer, limitation of indications within the insurance program, and the rational use of innovative anti-cancer medicines. It is necessary to improve relevant supporting policies to promote the affordability of patients. The government should speed up the process of price negotiation to include more innovative anti-cancer medicines in the medical insurance coverage, consider including both medical examinations and adjuvant chemotherapy in the medical insurance, and increase investment in health care.